Anticancer efficacy of silver nanoparticles synthesized from Erythrina variegata L. leaves extract against A549 lung cancer cell line - Halimatussakdiah, Halimatussakdiah; Mardina, Vivi; Amri, Yulida; Misdi, Misdi; Wahyuningsih, Puji; Tan, Siow-Ping (Penerbit Universiti Kebangsaan Malaysia, 2025)
Green synthesis using plant extracts as metal ion reducing agents is gaining attention for its eco-friendly approach. Silver nanoparticles (AgNPs) are widely studied for their ability to penetrate biological membranes, accumulate in organs, and exhibit anticancer activity. In this study, Erythrina variegata L. (Dadap) leaves extract was used as a natural reductant for AgNP synthesis. Phytochemical screening showed the presence of alkaloids, saponins, flavonoids, phenols, and tannins - compounds known for potential anticancer activity. UV-Vis spectrophotometry showed two main peaks within the 272-600 nm range. The peak at 272 nm indicates the presence of aromatic compounds, such as phenolics from the extract, which may be bound to the nanoparticle surface and function as reducing or stabilizing agents. The broader peak within 380-450 nm, commonly around 420 nm, corresponds to the surface plasmon resonance (SPR) of AgNPs, confirming their successful formation. FTIR analysis identified functional groups (-OH, -CH, C=O, C=C, and -NH) linked to phenolics, flavonoids, and alkaloids, along with Ag-O and Ag-N bonds indicating nanoparticle formation. XRD patterns confirmed an FCC crystal structure with characteristic peaks at 2θ = 38.1°, 44.2°, 64.5°, and 77.0°. TEM images showed spherical, well-distributed AgNPs, contrasting with the amorphous nature of the extract. Cytotoxicity tests on A549 lung cancer and Vero cells yielded IC50 values of 7.222 µg/mL and 3.488 µg/mL for the extract and AgNPs on A549 cells, and 9.4 µg/mL and 3.785 µg/mL on Vero cells, respectively. The selectivity index (SI) values of 1.3 and 1.09 indicate low selectivity and cytotoxic effects on both cell types. Although AgNPs showed stronger cytotoxicity against cancer cells, their non-selective toxicity suggests the need for further modification to enhance therapeutic safety